BEKASAM IKAN LELE DUMBO (Clarias gariepinus) DENGAN PENGGUNAAN SUMBER KARBOHIDRAT YANG BERBEDA - Ayu Kalista; Agus Supriadi; Siti Hanggita R.J. (Universitas Sriwijaya, 2012)
This purposes of this research were to determine the effect of different carbohydrat sources on the the characteristics of chemical, microbiological and organoleptic bekasam Â catfish. The research was conducted in June until July 2011 at Fishery Processing Technology Laboratory, Aquaculture Laboratory, Animal Nutrition Laboratory and Bioprocess Laboratory University of Sriwijaya.This research that the used Completely Randomized Design (CRD) with five treatments, and each treatment was replicated three times. The treatment were Â A1 = glutinous rice flour, A2 = corn flour, A3= wheat flour , A4 = cassava flour, A5 = rice flour.The result showed used of different carbohydrate sources had significant effect in N-amino content, pH value and total count but was significantly for water content and ash content. The highest bacterial count was obtained by using rice flour (4,491) and the lowest was found in bekasam with glutinous rice (3.470). The flour that has a higher amylose content is easier to use as a bacterial growth media. Based on sensory test, the best treatment was derived from rice flour and had a higher preference level aroma (3.64), tekstur (3.86) and apperance (3.27). The research recomended that bekasam that used rice flour had best physical, chemical and mikrobiology properties.